Pengabdian Masyarakat SMPN 4 Ungaran Pelatihan Kader Kesehatan Remaja Tentang Status Gizi Remaja Dan Deteksi Dini Masalah Kesehatan Reproduksi Remaja - Veftisia, Vistra; Afriyani, Luvi Dian; Salafas, Eti (Jurnal Pengabdian Dharma Bakti, 2020)
Teenagers are often classified as a group that is always healthy away from risk factors for illness, but many health problems suffered by adolescents due to behavioral factors that can actually be prevented. Teenagers are faced with complex problems related to physical, psychological and emotional changes that cause teens to experience health problems. Some health problems that often occur are nutrition and reproductive health. Prevention can be done if students make early detection of nutritional problems and adolescent reproductive health problems with the support of the environment both at home and at school. The obstacle that often occurs in schools is a fairly large comparison between the number of health service providers and the number of students in school. The role of adolescent health cadres to help adolescents be more comfortable discussing about nutrition and adolescent reproductive health issues. In connection with these problems, community service programs provide solutions to improve students' knowledge of adolescent nutritional status and early detection of adolescent reproductive health problems through training and mentoring of adolescent health cadres. The activity began with the training of adolescent health cadres totaling 18 grade 7 students through active learning learning methods. From these activities it was found there was an increase in the knowledge of adolescent health cadres after the training. The next activity was an accompanying adolescent health cadre to conduct health education with peers consisting of class 8 totaling 54 students. The result is an increase in knowledge. The next activity is the evaluation of activities with the school principal and Wa.Ka. students, and obtained results that this activity will be continued with other class targets using the media that has been given.Keywords: Health cadres, adolescent nutrition, adolescent reproductive health